Konstitusionalitas Kebijakan Asuransi Kesehatan Menteri Pensiunan Berdasarkan Keadilan Sosial dan Akuntabilitas Keuangan Negara - Nurchabibah, Reza; Waluyo (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
The health insurance policy for retired ministers as stipulated in Presidential Regulation No. 121/2024 has sparked controversy regarding fairness and its implications for state financial accountability. This study aims to analyze the suitability of this policy with the principles of social justice and state financial accountability in public budget management. The method used is normative juridical through statutory, conceptual and case-based approaches based on the general principles of good governance, especially the principles of justice, propriety, and public budget efficiency. The results show that this policy has the potential to create social injustice because it provides special facilities to political elites without objectively considering their economic conditions. In addition, this policy risks burdening the state budget disproportionately and disrupting essential public sector budget allocations. It is concluded that the policy has the potential to be tested through judicial review because it contradicts the principles of good state financial governance.